Origins Orginality + Beyond : The sixth Biennale of Sydney 1986. - Waterlow, Nick; Krauss, Rosalind; Lyotard, Jean-François; Restany, Pierre; Caroll, Flavio; Foster, Hal; McEvilley, Thomas; Grundmann, Heidi; von Graevenitz, Antje; Lawson, Thomas; Art Gallery of New South Wales, Sydney; The Sixth Biennale of Sydney, 1986 (Sydney : Biennale of Sydney, 1986)
Abakanowicz, Magdalena ; Adrian, Robert ; Anderson, Laurie ; Armleder, John ; Barcelo, Miguel ; Baxter, Glen ; BazileBustamante ; Beuys, Joseph ; Booth, Peter ; Brassil, Joan ; Brown-Rrap, Julie ; Byars, James Lee ; Cahn, Miriam ; Ceccobelli, Bruno ; Chlanda, Marek ; Coleing, Tony ; Cox, Stephen ; De Maria, Nicola ; Dimitrijevic, Braco ; Di Stasio, Stefano ; etc.
Origins Orginality + Beyond : The Sixth Biennale of Sydney 1986, Art Gallery of New South Wales, Art Gallery Road, Sydney, Pier 2/3 Walsh Bay, Sydney, 16 May - 6 July 1986
English
kunstcatalogus